Ķīnas tiešo investīciju Latvijā ilgtspēja - Urinov, Davronbek (Latvijas Universitāte, 2021)
Ķīnas tiešo investīciju Latvijā ilgtspēja. Pētījums ir par Ķīnas tiešajām investīcijām Latvijā. Tajā tiek analizēts, vai Ķīnas investīciju uzņēmumi Latvijā ir ilgtspējīgi. Ja viņi pilda saistības attiecībā uz korporatīvo sociālo atbildību, ja tie nekaitē videi. Tā kā Latvijā palielinās Ķīnas investīcijas, jāpārliecinās, ka tie nes peļņu, kā arī drošību.

Sustainability of Direct Investments from China in Latvia. The research is about Chinese direct investment in Latvia. It analyses whether China investment-based companies in Latvia are sustainable. If they do obligations in terms of corporate social responsibility, if they do not harm environment. Since Chinese investment is increasing in Latvia, it is necessary make sure that they bring profit as well as safety.
Sustainability of Direct Investments from China in Latvia
Keywords: Vadībzinātne; Sustainability and green investment; Foreign Direct investment; China; Latvia